Extranodal Rosai-Dorfman-Destombes disease mimicking renal cell carcinoma: a case report and review of literature - Nallabothula, Anil Kumar; Chilekampalli, Konda Reddy; Nalumaru, Anirudh Suseel; M, Harshavardhan Varma; Bhargava, Anupam; Jayanth, Ashish Kumar (International Surgery Journal, 2022)
Rosai-Dorfman-Destombes disease (RDD) is an uncommon histiocytic disorder of unknown aetiology. Extranodal involvement occurs in a significant proportion of patients but involvement of the kidney is rare. Here we present a case report of extranodal RDD of the kidney. Imaging revealed a heterogeneously enhancing solid mass lesion in left renal hilum infiltrating renal medulla and deeper layers of renal cortex. With the clinical diagnosis of suspected left renal cell cancer, laparoscopic left radical nephrectomy was performed. Macroscopic examination showed specimen covered with Gerota’s fascia and perinephric pad of fat. Renal capsule could be easily split off. On cut section, ill circumscribed solid lesion having variegated appearance with areas of necrosis and haemorrhage, involving middle and lower pole, was noted. Renal sinus appeared to be involved. Microscopic examination showed sheets of histiocytes with abundant eosinophilic to vacuolated cytoplasm. There was emperipolesis of intact lymphocytes. Also, seen were sheets of plasma cells, lymphocytes with intervening dense hyalinised stroma. Retro peritoneal lymph nodes and para-aortic lymph nodes also showed similar histological picture. Immunohistochemistry showed that the histiocytes were positive for S100 and CD68. IgG4-positive plasma cells were not seen. These findings showed that the lesion represented and extranodal RDD of the kidney. Although rare, extranodal RDD should also be included in the differential diagnosis of a renal mass and frozen section be advised whenever feasible.